Depressed lymphoproliferative response in mixed leukocyte reaction after Mis-locus alloimmunization (Revista Española de Fisiología, 1984)
The proliferation of BALB/C lymphocytes preimmunized with Mis or H-2 incompatible cells in response to alloantigens was studied.The results show that preimmunization with Mis-incompatible spleen cells inhibits the lymphoproliferative response against alloantigens whereas preimmunization with H-2 incompatible spleen cells enhances it.It is suggested that Mis coded determinants activate suppressor mechanisms responsible for the unresponsiveness of these preimmunized lymphocytes against alloantigens.